Предмет: Алгебра,
автор: polkovnykovadaryna
Перетворіть у многочлен вираз:
b(6b+7)(3b-4)=
-(6d-3)(2-8d)=
Ответы
Автор ответа:
1
1)
b(6b+7)(3b-4) =b(18b²-24b +21b-28) =
=18b³-24b²+21b²-28b=18b³-3b²-28b
b(6b+7)(3b-4) =b(18b²-24b +21b-28) =
=18b³-24b²+21b²-28b=18b³-3b²-28b
water58work:
2 не смог решить
Похожие вопросы
Предмет: Математика,
автор: Alinachkkaaa11
Предмет: Українська мова,
автор: tkudinova09
Предмет: Алгебра,
автор: Chtoooi8273838
Предмет: Другие предметы,
автор: kobcevaelena
Предмет: Математика,
автор: Zelenajksnigana